ANALISIS STRUKTUR JEMBATAN CABLE-STA FED AKIBAT BEBAN GEMPA - Ramdani, Yusep
Abstract: The characteristic of earth quake can 't be predicted accurately, one of the way to anticipate is by building the structure that has behaviour and character in enduring toward quake loads. The process of spreading of quake load toward structure of cable stayed bridge is started from the pylon as cable arrangement support that has direct relation with the foundation. Then the pylon distribute it at cable element and deck of cable stayed bridge. This thesis explaine the case study of bridge structure in total length of bridge are 1520 m, length of central are 760 m, the total high of pylon are 225 m and the diameter of cable are 0,25 m. the analysis of spectra respon is done for reduction factor of quake load (R) 1, 1,6, 4 and 8,5 with modal analysis method While the analysis of time history is done by using the simulation of quake speed with step integration method. In analysis of spectra respon shows the result of intern forces are more consistent than analysis of equivalent static. The scores of base shear in time history analysis show strong quake without quake load reduction (R). The displacement of deck and pylon that is resulted by analysis time history is smaller than analysis of soectra respon with quake reduction factor (R) = 1,6.